History, Bhakti, and public memory : Namdev in religious and secular traditions - Novetzke, Christian Lee (Permanent Black, 2009)
Namdev is central figure in the cultural history of India, especially within the field of bhakti, a devotional practice that has created public of memory around the figure of Namdev for over eight centuries. Born in the Marathi-speaking region of the Deccan in the late thirteenth century, Namdev is remembered as a simple, low-caste Hindu tailor whose innovative performance of devotional songs spread his fame widely. He is center to many religious traditions within Hinduism, as well as to Sikhism, and he is a key early literary figure in Maharashtra, northern India, and Punjab. In the modern period, Namdev appears throughout the public spheres of Marathi and Hindi and in India at large, where his identity fluctuates between regional associations and a quiet, pan-Indian, nationalist-secularist profile that champions the poor, oppressed, marginalized, and low caste. Christian Lee Novetzke considers the way social memory coheres around the figure of the Namdev from the sixteenth century to the present, examining the practices that situate Namdevs memory in multiple historical publics. Focusing primarily on Maharashtra and drawing on ethnographies of devotional performance, archival materials, scholarly historiography, and popular media, especially film, Novetzke vividly illustrates how religious communities in India preserve their past and, in turn, create their own historical narratives. Preface This book is about how a religious figure of fourteenth-century India has been remembered over seven centuries, through multiple media, including performance, writing, and film. The figure is Namdev, a sant important to Hindus and Sikhs in central, western, and northern India. The book focuses primarily on the cultural history of Namdev's legacy in the area coterminous with modern-day Maharashtra. The theoretical rubrics used to understand this